E-Evaluation Development Using Hot Potatoes Software in English Subjects with Profession Material in Grade V of Elementary School Academic Year 2021/2022 - Zurriyana Nainggolan; Eva Betty Simanjuntak; Dedek Oktavia Nasution; Hamka (Universitas Islam Negeri Palopo, 2026)
This study aimed to determine the feasibility and practicality of e-evaluation using Hot Potatoes software in English subjects on profession material for fifth-grade students at Elementary School. The research used a Research and Development (R&D) method with the ADDIE model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were fifth-grade students, while the object was the e-evaluation media developed using Hot Potatoes software. The results showed that the media was highly feasible, as indicated by media expert validation results of 89% and material expert validation results of 90%, both categorized as “very feasible.” The practicality of the media was also proven through practitioner assessments, which obtained a score of 93% and were categorized as “very practical.” In addition, student response questionnaires in small-group trials showed an average score of 91.6%, indicating that the media was very practical and easy to use. The field-trial results further showed an increase in students’ learning outcomes, with the average pre-test score of 57.50 rising to a post-test average of 76.88 after the use of the Hot Potatoes-based e-evaluation. Therefore, it can be concluded that e-evaluation using Hot Potatoes software is feasible and practical for use in learning activities for fifth-grade students at Elementary School.